Penerapan Prinsip Inviolabilitas Dan Ekstrateritorial Dalam Hukum Diplomasi Dan Konsuler (Studi Kasus Penerobosan Gedung Konsulat Rusia Oleh Amerika Serikat) - Ari Wibowo, Septian; Nofendi, Mohammad; Widjaksono, Aditya Muyarajasa; Sutiyono, Agus; Birahayu, Dita (Jurnal Hukum Positum, 2024)
Consular relations are part of foreign relations that are a necessity for every country. Both the receiving and sending countries have their respective obligations under international law. The purpose of this study is to find out about the regulation of the principles of inviolability and extraterritoriality in international diplomatic law and its application to America's actions in entering the empty Russian consulate building in Seattle. This study was conducted using a normative legal method using 3 (three) approaches, including the statute approach, conceptual approach, and case approach. The United States as the receiving country in this study violated the principles of inviolability and extraterritoriality by breaking into the empty Russian consulate building in Seattle. America should respect the principles of inviolability and extraterritoriality by bringing in a third party as a neutral party and at that time there was no urgent condition or extraordinary event (force majeure). America itself ratified the 1963 Vienna Convention on diplomatic law so that America can be declared to have violated the principles of international lawWritten in English, Open Sans, 10 pt, justify, 1 space, maximum 150 words, contains the background of the problem, the urgency of writing/research, research methods, research results, and conclusions. The abstract is written in one paragraph, without references, without abbreviations/acronyms, and without footnotes.